Designing antimicrobial active packaging films based on chitosan plus fungus comb ethyl acetate extract from Indo-Malayan termite mounds - LUCIA DHIANTIKA WITASARI; DEBORAH PATRICIA LIZAR; OLIVIA MARTHA FLORENCIA; ARIF RAMADHAN; NUR AFNI OKTRI FIANA; SUPRIYADI SUPRIYADI; SYLVIA UTAMI TUNJUNG PRATIWI; DODI NANDIKA; LINA KARLINASARI; ARINANA ARINANA; IRMANIDA BATUBARA; DJOKO SANTOSO; I KETUT SUDIANA; DECSA MEDIKA HERTANTO; YANTI RACHMAYANTI; DIKHI FIRMANSYAH (Society for Indonesian Biodiversity, 2023)
Abstract. Witasari LD, Lizar DP, Florencia OM, Ramadhan A, Fiana NAO, Supriyadi S, Pratiwi SUT, Nandika D, Karlinasari L, Arinana A, Batubara I, Santoso D, Rachmayanti Y, Firmansyah D, Sudiana IK, Hertanto DM, Rachmayanti Y, Firmansyah D. 2023. Designing antimicrobial active packaging films based on chitosan plus fungus comb ethyl acetate extract from Indo-Malayan termite mounds. Biodiversitas 24: 5947-5955. Antimicrobial active packaging systems incorporate antimicrobial compounds into polymer films, i.e., chitosan, thus suppress spoilage microorganism growth in foods. Chitosan films itself cannot prevent microbial growth, thus other antimicrobial agent must be added. Fungus comb extract from Indo-Malayan termite (Macrotermes gilvus (Hagen, 1858)) mounds is a potential active organic antimicrobial compound, which can be incorporated into chitosan films. The purpose of this study was to develop and characterize active packaging films based on chitosan plus an antimicrobial fungus comb ethyl acetate extract. Films contained 1% chitosan and fungus comb ethyl acetate extract (0.5, 1, 2, and 5% w/v). Notably, films containing 2 and 5% extracts inhibited Escherichia coli (ATCC 25922), Staphylococcus aureus (ATCC 25923), and Pseudomonas aeruginosa (ATCC 27853), but not fungi. Films plus 2% extract showed a thickness, tensile strength, and strain of 0.13 mm, 2.15 MPa, and 32.55%, respectively. Films had a moisture content of 0.26%, water solubility of 2.68%, swelling property of 2.37%, and water vapor permeability (WPV) of 3.31×10?10 g.m?1s?1.Pa?1. They displayed smooth morphology but no new functional groups. Thus, chitosan plus 2% of fungus comb ethyl acetate extract can be used in antimicrobial active packaging films for food application. It could be applied as a green alternative to prolong the shelf-life of food products.